Factors Affecting Outcome of Patients with Upper Gastrointestinal Haemorrhage Presenting to Emergency Department: A Prospective observational cohort study - Lal, Devakrishna Bhavan; Ekka, Meera; Yadav, Rupesh; Yadav, Amlendu; Kumar, Sandeep (Journal of Anaesthesia and Pain, 2023)
Background: Upper gastrointestinal bleeding (UGIB) is one of the most common presentations in an emergency department (ED). UGI endoscopy is the definitive diagnostic and therapeutic modality for UGIB. Aim of the study were look into the outcomes of UGIB and outcomes based on the timing of endoscopy (early endoscopy mean before 24 hours and late endoscopy mean after 24 hours).Methods: 180 patients presented in ED with UGIB and undergo Upper gastrointestinal (UGI) endoscopy. Socio-demographic profiles, with presenting signs and symptoms, co-morbidities, vitals, lab parameters, endoscopic diagnosis with the treatment of the patient were collected. They were followed up to day 7 of presentation to determine all-cause mortality, re-bleed, development of hemorrhagic shock, admission rate and length of ED stay, early endoscopy and late endoscopy.Result: The mortality difference in the early endoscopy (3.2%) and late endoscopy (16.1%) group was significant with a p-value of 0. 012. Late endoscopy (18.6%) was associated with a higher risk of development of hemorrhagic shock compared to the early group (4.8%) with a p-value of 0.011. The factors that had a significant association with mortality on univariate analysis were, late endoscopy, systolic blood pressure on presentation less than 90, variceal bleeding, blood transfusion requirement, AIMS 65 score greater than 0. Multivariate analysis showed that late endoscopy (OR 5.35(1.12-25.3)) and AIMS 65 score (OR 11.76(1.48-93.3)) were independent risk factors for mortality.Conclusion: We concluded that early endoscopy was associated with decreased mortality, decreased length of ED stay and decreased risk of development of hemorrhagic shock.